Conceptional design of a decentralised control environment for track based automatedguided vehicles - Can Ulas (Conceptional design of a decentralised control environment for track based automatedguided vehicles, 2019)
In recent years, blockchain technology in connection with industrial applications has increasingly moved into the focus of production. Blockchain technology deals with the decentralisation of data in a non-trusted environment. Another unique selling point is the unchangeability of the data, once it has been published. In this thesis, the fundamentals of blockchain as well as the fundamentals of decentralisation of production processes and automated guided vehicle systems are examined. The feasibility and implementation of such an environment is presented by means of an industrial application using a selected example. The aim is to check, whether the combination of these technologies can generate added value for industry. For this purpose, a concept will be developed and investigated upon the discussed application.